“Peace” in the Quran Text: a Look at the Significance and Purports (The Verbal Noun as a Model) | (السّلام في النّص القرآنيّ: نظرات في الدّلالة والمقاصد (المصدر نموذجًا - Nahla Alshalabi; Tar Abdallahi (Al-Zahra: Journal for Islamic and Arabic Studies)
The study aims to determine the singificance and purport of the use of the verbal noun (سلام peace) given the linguistic kinship between language and style in the context of the Qur'anic discourse.